Analysis Of Financial Performance And Service With Hospital Independence In Rumah Sakit Daerah K.R.M.T Wongsonegoro Kota Semarang - Nadia Dwi Irmadiani (Universitas 17 Agustus 1945, 2023)
The objective of this study is to examine the financial and service performance of the K.R.M.T Wongsonegoro Regional Hospital in Semarang City, which has been utilizing the Regional Public Service Agency Financial Management Pattern (PKK-BLUD) since 2007. By transitioning into a full (BLUD), the Semarang City RSWN has gained the ability to handle its finances independently, hence enhancing its performance and service quality. The present study incorporates quantitative research employing a time series methodology. The data utilized in this study consists of secondary data obtained from financial records and hospital management reports. The assessment of financial performance is conducted through the utilization of financial measures, encompassing liquidity ratios, solvency ratios, and profitability ratios. In the context of service evaluation, the measurement of service performance encompasses six distinct indicators. These indicators include the Bed Occupancy Rate (BOR), Turn Over Interval (TOI), Bed Turn Over (BTO), Average Length of Stay (ALOS), Gross Date Rate (GDR), and Net Date Rate (NDR). The research hypothesis was examined by the application of Pearson correlation. The findings of the study indicate a significant correlation between financial performance, as assessed by the solvency ratio, and both the cost recovery rate and level of independence. The level of independence exhibits a significant link with service performance, as assessed by BTO.